Sequence conservation from human to prokaryotes of Surf1, a protein involved in cytochrome c oxidase assembly, deficient in Leigh syndrome. - Poyau, A.; Buchet, K.; Godinot, C. (FEBS Letters, 1999)
The human SURF1 gene encoding a protein involved in cytochrome c oxidase (COX) assembly, is mutated in most patients presenting Leigh syndrome associated with COX deficiency. Proteins homologous to the human Surf1 have been identified in nine eukaryotes and six prokaryotes using database alignment tools, structure prediction and/or cDNA sequencing. Their sequence comparison revealed a remarkable Surf1 conservation during evolution and put forward at least four highly conserved domains that should be essential for Surf1 function. In Paracoccus denitrificans, the Surf1 homologue is found in the quinol oxidase operon, suggesting that Surf1 is associated with a primitive quinol oxidase which belongs to the same superfamily as cytochrome oxidase.